Summer Camp for Experimental Archaeology in the Eindhoven Museum (NL) - Lasse van den Dikkenberg (EXARC Journal)
Every year the Dutch Youth Association for History (NJBG) organizes several summer camps for children and young adults. Since the Eindhoven Museum was founded in 1982 the Workgroup for Experimental Archaeology (WEA) has organised activities in the museum which are concerned with experimental archaeology. This year a group of young adults (age 16-26) stayed for one week (27th July – 2nd August 2015) in the Eindhoven Museum where they conducted several experiments.